Rethinking Clinical Trials and Redefining Responsibility for Research Participants: A Focus on Africa - Iyioke, Ike (Ethics International Press Limited, 2023)
This is a new treatment of clinical research ethics in an African context, and an indispensable resource for researchers, students, policy makers and research institutions interested in African research ethics. In re-appraising the African philosophical notion of selfhood, it argues for the need to re-conceptualize responsibility in clinical trials, pushing researchers to go beyond autonomy-based considerations based on the individual only, and to develop clinical trials that appropriately embed research subjects within their community and their environment. The African standpoint stresses communalism and communitarianism. As such, responsibility for, and by, the individual can only make sense through the community in which the individual is rooted. The book emphasizes the African viewpoint by making explicit the importance of the self in the re-contextualized arena of the community. It forces research ethicists to go beyond autonomy-based considerations for the individual only, and to appropriately embed research subjects within their community and their environment.